Open access for all: how to design an inclusive and diverse open scholarly communication system (Pubmet, 2022)
The recent success of open access across the scientific landscape may hide strong inequalities among scientific communities in terms of adoption of open scholarly communications. It is a fact that concerns regarding equity, diversity and inclusion are quite recent in the community. Then, how should we try to redesign open access to address these concerns? The talk will aim at suggesting potential solutions and open a discussion with the audience.